Pengembangan Model Penyusunan Kurikulum Tingkat Satuan Pendidikan (KTSP) yang Mengacu pada Standar Nasional Pendidikan - Halimah, Lely; Rostika, Deti; Sudirjo, Encep (Universitas Pendidikan Indonesia, 2009)
This research is performed due to the presence of gap between the policy in the improvement of curriculum and the existing fieldâ€condition in elementary school. On one side Schoolâ€Based Curriculum (KTSP) is expected to be applied in schools autonomously, on the other hand, neither the principals nor the teachers, especially of elementary schools, have had comprehensive understanding on the concept of Schoolâ€Based Curriculum, its construction process, as well as the implementation. The problem of this research, therefore, is â€How is a model for the construction of Schoolâ€Based Curriculum that refers to National Education Standard developed to result in Schoolâ€Based Curriculum (KTSP) documentâ€?With reference to the above mentioned background, this research is purposed to offer facilities to schools, especially elementary schools, in the process of constructing Schoolâ€Based Curriculum that refers to the guideline of KTSP construction by Badan Standar Nasional Pendidikan (National Standard Agency for Education), so that they can have KTSP document. In other words, this research will result in a product of the process of Schoolâ€Based Curriculum (KTSP) model development for KTSP document.Â Â Â In order to achieve the objectives, this research is conducted using Research and Development approach.Â Â In the implementation, this research and development forms a cycle, which begins with a preliminary study to find an early product required. This early product is then developed in a certain condition, with a test, the result of which is revised and retested until the final product, which is considered satisfactory, is obtained. The validity of this final product is then examined. This research is conducted in elementary schools in Cileunyi District of Bandung Regency, of which the principal and the teachers become the subject of this research.Â Â Referring to the Research and Development measures, as mentioned above, the process of constructing Schoolâ€Based Curriculum (KTSP) contains two stages. The first stage is the work discussion of the team that consists of Headmaster as the chairman, teachers, and school committee, and involves related parties from the Subdistrict Office of National Education Department and experts (in this case: the research team), which produces book 1 containing general guideline of Schoolâ€Based Curriculum (KTSP) development. The second stage is the work discussion of the research team, Headmaster, and teachers, which produces book 2 consisting of six copies of books for each grade, from the first to the sixth.Â Â Suggestions put forward in this research is that the socialization of Schoolâ€Based Curriculum (KTSP) should be carried out in whole and applicable so as to give clear description of the process and product of Schoolâ€Based Curriculum (KTSP) construction to those school, since they â€“elementary schools in particularâ€Â have not been able to create Schoolâ€Based Curriculum (KTSP) autonomously.